REVIEW ON THE MONOGRAPH ANTONYUK N.O. «DIFFERENTIATION OF CRIMINAL LIABILITY IN CRIMINAL LAW OF UKRAINE» (Bulletin of criminological association of Ukraine, 2023)
The problem related to the differentiation of criminal liability is one of the basic ones for criminal law. After all, the differentiation of criminal responsibility is closely intertwined with all institutions of criminal law. Therefore, the study of both the very concept of this phenomenon and the types and means of differentiation is important both for the science of criminal law and for law enforcement practice. Questions related to the differentiation of criminal responsibility have always been relevant in the doctrine of criminal law.
Keywords: REVIEW